EFFECT OF MOTHER TONGUE TEACHING STRATEGY ON ACADEMIC ACHIEVEMENT OF JUNIOR SECONDARY SCHOOL STUDENTS IN MATHEMATICS IN IJEBU ODE, OGUN STATE (UNIZIK Journal of STM Education, 2022)
The study examined the effect of mother tongue teaching strategy on academic achievement of junior secondary school students' in mathematics. The purpose was to examine the effect of mother tongue teaching strategy on academic achievement of junior secondary school students' in mathematics, to examine the effect of gender on academic achievement of junior secondary school students' in mathematics and to examine the interaction effects between mother tongue teaching strategy and gender on academic achievement of junior secondary school students' in mathematics. The study adopted a pre−test, post−test and control group quasi experimental design. 150 students drawn from junior secondary schools in Ogun State were sampled and used for the study using purposive sampling techniques. A unified scheme of work for the students was utilized for the study. Mathematics Achievement Test (MAT) was used to collect data on students’ achievement, which was validated by the school mathematics teachers, its reliability was ascertained by using split half method and the coefficient obtained was 0.77. The data obtained from the respondents were collated and analyzed using ANCOVA (Analysis of Co-variance). Findings revealed that there is a significant main and interaction effect of mother tongue teaching strategy, mother tongue and gender on the academic achievement of the students’ in mathematics. Based on the findings it is recommended among other things that mother tongue should be employed in the teaching and learning process at junior secondary school level in order to internalize the love for mathematics and make the students mathematics friendly at their age.
Keywords: Gender; Mother tongue; Mathematics; Academic Achievement; students